2020
DOI: 10.1186/s12991-020-00264-9
|View full text |Cite
|
Sign up to set email alerts
|

Higher dietary fat quality is associated with lower anxiety score in women: a cross-sectional study

Abstract: Background: The relationship between anxiety and dietary fat quality (DFQ) has not been well studied. The aim of this study was to investigate the relationship between anxiety disorder and fatty acids' intake in women. Methods: This cross-sectional study included 300 women aged 18-49 attending healthcare centers. Dietary exposure was measured by a 168-item semi-quantitative food frequency questionnaire (FFQ). To determine the status of anxiety, the Depression, Anxiety, and Stress Scale (DASS) questionnaire was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…In humans, a number of lifestyle factors are associated with anxiety, including diet. For instance, consumption of added sugars and saturated fat is associated with higher anxiety levels ( Masana et al, 2019 ; Fatemi et al, 2020 ), and evidence from carefully controlled rodent experiments suggests a causal relationship between diet and anxiety-like behavior. In rodents, anxiety-like behavior is assessed via measurable behavioral changes, including measures of exploration, hypoactivity, suppressed consumption of novel foods (neophagia), and fear-associated freezing behavior.…”
Section: Anxiety-like Behaviormentioning
confidence: 99%
“…In humans, a number of lifestyle factors are associated with anxiety, including diet. For instance, consumption of added sugars and saturated fat is associated with higher anxiety levels ( Masana et al, 2019 ; Fatemi et al, 2020 ), and evidence from carefully controlled rodent experiments suggests a causal relationship between diet and anxiety-like behavior. In rodents, anxiety-like behavior is assessed via measurable behavioral changes, including measures of exploration, hypoactivity, suppressed consumption of novel foods (neophagia), and fear-associated freezing behavior.…”
Section: Anxiety-like Behaviormentioning
confidence: 99%
“…Based on this, the brain is highly vulnerable to functional impairment from nutrient imbalances, influencing the development and progression of psychiatric disorders. Several reports have confirmed that excessive intake of saturated fats and refined carbohydrates promotes defective behaviors and susceptibility to mental disorders in both animal models and humans (Fatemi et al, 2020;Y. Li et al, 2022;Łojko et al, 2018;Quirk et al, 2013;Zemdegs et al, 2016).…”
Section: Die T Modul Ate S Cer Amide S Me Tabolis M and Suscep Tib Il...mentioning
confidence: 92%
“…In contrast, low-fat diets were found to be related to greater anger and hostility for humans aged 20-37 [16]. There also seems to be a difference in results based on the type of fat consumed—while saturated fatty acids are positively associated with anxiety [17], unsaturated fatty acids, such as α-linolenic acid, were correlated with reduced likelihood for anxiety and depression [17,18]. Lastly, a few studies found no association between the level of fat consumption and mental health status or mood [19,20].…”
Section: Introductionmentioning
confidence: 99%